Users' psychological perception and perceived readability of wearable devices for elderly people. Issue 3 (3rd March 2016) - Fang, Yu-Min; Chang, Chien-Cheng
ABSTRACT: As the population of elderly people in society rises, the importance of technology to assist health management is growing with the demographic shift. Wearable personal computing has been the common solution proposed by related projects to fulfil the needs of elderly people. These add-on devices are attached to the users, and result in uneasiness or discomfort while wearing them in public areas. In this study, three common wearing positions – wrist, upper arm, and neck – were investigated in terms of psychological perception and perceived readability. Twenty-four Taiwanese participants in Miaoli area were asked to wear the designed prototypes for a certain time. The participants completed questionnaires and participated in an open-ended interview. Data of psychological perceptions, visibility, and readability about wearable devices were collected. The results evidenced that the personal attributes of gender, smart device user, and requirement for medical care affect the psychological perception and user attitudes. The statistical results indicated significant differences in elderly people's attitudes towards wearable devices attached to different parts of the body. The wrist was the most favourable location to attach a wearable device.